Educação em ciências nas práticas pedagógicas de educação infantil - Aikawa, Monica Silva (2014)
This dissertation entitled Science Education in pedagogical practices of early childhood education, linked to the Post Graduate Program in Science education in the Amazon, has its purpose directed by the following scientific problem: How the educational concepts in science are given in the pedagogical practices of professionals working in preschool classes at a CMEI in Manaus? Thus, the overall objective is to analyze the concepts of science education and their effect on the pedagogical practices of teachers of early childhood education in preschool classes of CMEI Maria do Céu. We show how specific objectives of the research verifying the design of teachers from preschool classes on child education and science education; identify the concepts of science education expressed in the pedagogical practices of teachers of CMEI. We based our methodological path in qualitative approach of educational research, opting for interviews with teachers and observation of their teaching in preschool classes. The analyses procedures were performed with reference to the content analysis. The results and discussions highlight that teachers are undergoing restructuring of their teaching in the further development and justification of their conception of early childhood education. About science education, teachers understand as a perspective of environmental education and they implement some pedagogical practices involving the sciences in their reintegration nuances as culture and education of the citizen. However, we found by searching the lack of experiences proposition with the sciences that lead children to experience scientific concepts and research building processes